What is the Meaning of an Automobile for the Consumer? How Brazilians and Americans Evaluate Cars, a Comparative Model - Breno Giovanni Adaid-Castro (FUCAPE Business School, 2019)
The objective of this study was to identify the relation between Human Values and behavior in order to judge automobile purchases in Brazil and the United States of America. North Americans (N=461) and Brazilians (N=570) filled out the Portrait Values Questionnaire in its refined version, PVQ-R (Schwartz et al., 2012), the List of Values (Kahle & Kennedy, 1988) and the Judgment and Meaning Scale (Allen, 2000). Using stepwise regressions to determine which Human Value relates better with each type of judgment and attribution of meaning, two structural models were built comparing the influence of each value in each type of judgment both in the United States of America and Brazil. The results showed that in both countries the Human Values have a higher correlation with judgment than the List of Values and can predict the types of judgment and attribution of meaning the subjects use to evaluate automobile purchase, however, the structures are similar but not equal, indicating that cultural influences can alter how the evaluation is processed.